PAPPERLES OFFICE DI KANTOR KUA MEDAN BARU - Samsudin, Samsudin; Sukron, Muhammad; Pane, Rizky Hidayat (Smart Education, 2024)
Abstract: This study discusses the design of a goods storage information system at the Medan Class A Search and Rescue Office to improve the efficiency and accuracy of goods management management. This system is designed to automate the process of storing and tracking goods, which has been done manually and often causes various problems such as tracking difficulties and data inaccuracies. The results of the implementation show that this information system is able to minimize errors, reduce the risk of loss of goods, and ensure the availability of important equipment in real-time. Despite challenges such as user resistance and resource requirements, careful planning and proper training overcame these obstacles. In conclusion, this system contributes significantly in improving the operational performance of the Medan Class A Search and Rescue Office. Keywords: Goods, Information Systems, Storage, Office Abstrak: Kantor Urusan Agama (KUA) memiliki peran penting dalam penyelenggaraan pernikahan di Indonesia. Salah satu tugas utama KUA adalah mengelola dokumen pernikahan dengan baik dan efisien. Sistem pengarsipan dokumen yang efektif dan efisien sangat penting untuk menunjang kelancaran tugas KUA. Teknik pengumpulan data dilakukan melalui observasi, wawancara dan studi dokumen. Hasil penelitian menunjukkan bahwa KUA Medan Baru menghadapi keterbatasan ruang penyimpanan, kurangnya pemanfaatan teknologi informasi dan kebutuhan akan peningkatan pelatihan bagi staf. Untuk mengatasi masalah ini, dibangunnya sistem pengarsipan dokumen dengan tujuan meningkatkan kualitas layanan, efisiensi operasional dan keamanan dokumen di KUA Medan Baru. Kata kunci: Pengarsipan, Dokumen, KUA, Sistem